Effect of pH on the color thermal degradation of Clitoria ternatea anthocyanin-impregnated Whatman paper: A study on its potential as high-temperature colorimetric indicator - Margareta Mika; Hariyadi Purwiyatno; Suyatma Nugraha Edhi; Marpaung Abdullah Muzi (BIO Web of Conferences)
Clitoria ternatea flowers are a readily extractable source of anthocyanin. This study aimed to understand the effect of pH (5, 7, and 8) on the thermal stability of anthocyanin-impregnated Whatman paper (AIP) at elevated temperatures (80, 90, and 98 °C). Color degradation, expressed in terms of Chroma, was monitored using the CIE Lab color model (a*, b*, and C*). The results showed that the degradation rate increased with pH and temperature, with degradation rate constants at 80, 90, and 98°C for AIP5, AIP7, and AIP8 being 0.0004, 0.0010, 0.0018; 0.0015, 0.0041, 0.0059; and 0.0031, 0.0047, 0.0065 min-1, respectively. This indicates that pH 8 is the most unstable, so it causes the highest amount of color change. Activation energies were highest for AIP5 (89.35 kJ/mol), indicating that pH 5 is the most responsive to change in reaction rate with temperature fluctuations compared to AIP7 (82.26 kJ/mol) and AIP5 (43.70 kJ/mol). These findings suggest that AIP8’s rapid degradation at high temperatures makes it a potential candidate for high-temperature indication, while AIP5’s greater temperature sensitivity could be exploited for applications requiring the detection of smaller temperature variations.